Evaluation of growth and yield of selected hybrid and inbred rice varieties grown in net-house during transplanted aman season (Bangladesh Journal of Agricultural Research, 2010)
Pot experiments were conducted during T. aman 2001 and 2002 (wet season) at Bangladesh Rice Research Institute (BRRI) in net house. Hybrid variety Sonarbangla-1 and inbred modern variety BRRI dhan-31 were used in both the seasons and BRRI hybrid dhan-l was used in 2002. The main objective of the experiments was to compare the growth and yield behaviour of hybrid and inbred rice varieties under controlled condition. In 2001, BRRI dhan-3l had about 10-15% higher plant height, very similar tillers/plant, 15-25% higher leaf area at all days after transplanting (DAT) compared to Sonarbangla-1. Sonarbangla- 1 had about 40% higher dry matter production at 25 DAT but had very similar dry matter production at 50 and 75 DAT, 4-11% higher rooting depth at all DATs, about 22% higher root dry weight at 25 DAT, but 5-10% lower root dry weight at 50 and 75 DAT compared to BRRI dhan-31. The photosynthetic rate was higher (20 μ mol m-2/sec-1) in BRRI dhan-3l at 35 DAT (maximum tillering stage) but at 65 DAT, Sonarbangla-l had higher photosynthetic rate of 19.5 μ mol m-2 sec-1. BRRI dhan-3l had higher panicles/plant than Sonarbangla-1, but Sonarbangla-1 had higher number of grains/panicle, 1000-grain weight and grain yield than BRRI dhan-31. In 2002, BRRI dhan-31 had the highest plant height at 25 DAT, but at 75 DAT, BRRI hybrid dhan-l had the highest plant height. Sonarbangla-1 had the largest leaf area at 25 and 50 DAT followed by BRRI dhan-31, but at 75 DAT, BRRI dhan-31 had the largest leaf area. The highest shoot dry matter was observed in BRRI dhan-31 followed by Sonarbangla-1 at all DATs. Sonarbangla-1 had the highest rooting depth and root dry weight at all DATs. BRRI dhan-31 gave the highest number of panicles/plant followed by Sonarbangla-I, BRRI hybrid dhan-l had the highest grains/panicle followed by BRRI dhan-31 and Sonarbangla-I had the highest 1000-grain weight followed by BRRI dhan-31. The highest amount of grains/plant (34.6 g) was obtained from BRRI dhan-31. Key Words: Shoot dry matter; root dry weight; leaf area; photosynthesis; grain yield. DOI: 10.3329/bjar.v34i1.5755Bangladesh J. Agril. Res. 34(1) : 67-73, March 2009